2021
DOI: 10.1111/ppc.12758
|View full text |Cite
|
Sign up to set email alerts
|

Orthorexia tendency and social media addiction among candidate doctors and nurses

Abstract: Purpose To determine orthorexia tendency and social media addiction among candidate doctors and nurses. Design and Methods This was a cross‐sectional study conducted in 2019 with 969 candidate doctors and nurses training in a peripheral public university. Data were collected via ORTO‐15 and Social Media addiction scales and analyzed by using percentage, mean, χ 2 test, and binary logistic regression. Findings Of the study population, 78.8% were social media addicts and 62.2% had orthorexic tendencies. The rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 31 publications
1
9
0
1
Order By: Relevance
“…People using this platform were more likely to develop ON. Similar observations about orthorexia and the use of social media were made by Yılmazel [36]. It can therefore be concluded that social media, especially those rich in profiles focusing on the topic of healthy eating, contribute to the creation of inappropriate eating habits.…”
Section: Risk Factors Of Orthorexiasupporting
confidence: 69%
“…People using this platform were more likely to develop ON. Similar observations about orthorexia and the use of social media were made by Yılmazel [36]. It can therefore be concluded that social media, especially those rich in profiles focusing on the topic of healthy eating, contribute to the creation of inappropriate eating habits.…”
Section: Risk Factors Of Orthorexiasupporting
confidence: 69%
“…One study found that nurses in Turkey were also affected by SMA ( Hosgor et al, 2021 ), but there were no studies in the physician population for reference. In addition, many studies in college students found that the incidence of SMA was already higher among medical staff during their school years ( Turan et al, 2021 ; Yilmazel, 2021 ; Ilter and Ovayolu, 2022 ). The scores for mood modification (3.210 ± 1.048) and tolerance (3.231 ± 1.197) were the highest, indicating that medical care professionals mainly use social media to avoid work problems and relieve anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…The results yielded 15 studies ( Table A1 in Appendix A ) that address social media literacy by either conceptualizing it, or by referring to the competences of which it consists. It should be noted that there are studies that, despite using the concept in their articles, do not develop it, or they use it to talk about another type of literacy without making a suitable distinction on the issue [ 22 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%